PlumX from Plum Analytics: Not Just Altmetrics. Issue 1 (2nd January 2016) - Lindsay, J. Michael
ABSTRACT: Alternative metrics, or Altmetrics have been a topic of increased interest for librarians and other academics for some time, but how these measures can be integrated with traditional metrics has been unclear. Plum Analytics' PlumX Metrics integrates traditional measures such as citations, and shows them alongside Altmetrics, including electronic usage data, bookmarks, blog posts and social media measures to show a more complete picture of scholarly impact. This review will provide a profile of the features and capabilities of this resource.